Mapping hotspots of tuberculosis cases with validation on site in Gombak, Selangor, Malaysia - Nur Adibah Mohidem; Malina Osman; Zailina Hashim; Farrah Melissa Muharam; Saliza Mohd Elias; Aminuddin Ma’pol (Springer, 2024)
Indexed by WOS/Scopus